Hydromonas duriensis gen. nov., sp nov., isolated from freshwater - Ivone Vaz Moreira (2015)
An aerobic, Gram-stain-negative rod, designated strain A2P5(T), was isolated from the Douro river, in Porto, Portugal. Cells were catalase- and oxidase-positive. Growth occurred at 15-30 degrees C, at pH 6-8 and in the presence of 1 % (w/v) NaCl. The major respiratory quinone was Q8, the genomic DNA had a G+C content of 47 +/- 1 mol%, and phosphatidylethanolamine, phosphatidylglycerol and diphosphatidylglycerol were amongst the major polar lipids. On the basis of 16S rRNA gene sequence analysis, strain A2P5(T) was observed to be a member of the family Burkholderiaceae, but could not be identified as a member of any validly named genus. The low levels of 16S rRNA gene sequence similarity to other recognized taxa (< 91 %), together with the comparative analysis of phenotypic and chemotaxonomic characteristics, supported the proposal of a novel species of a new genus within the family Burkholderiaceae. The name Hydromonas duriensis gen. nov., sp. nov. is proposed. The type strain of Hydromonas duriensis is A2P5(T) (=LMG 28428(T) =CCUG 66137(T)).